Relationship between hydrothermal temperatures and structural properties of CeO2 and enhanced catalytic activity of propene/toluene/CO oxidation by Au/CeO2 catalysts - Eaimsumang, Srisin; Chollacoop, Nuwong; Luengnaruemitchai, Apanee; Taylor, Stuart H. (Frontiers in Chemistry, 2022)
A simple hydrothermal synthesis of CeO2 was implemented to obtain a series of CeO2-supported gold (Au) catalysts, used for the total oxidation of propene/toluene/CO gas mixtures and the oxidation of CO. CeO2 preparation started from a cerium hydrogen carbonate precursor using a range of different hydrothermal temperatures (HT) from 120°C to 180°C. High-resolution transmission electron microscopy, X-ray diffraction, and H2-temperature-programmed reduction data indicated that CeO2 morphology varied with the HT, and was composed of the more active (200) surface. Following Au deposition onto the CeO2 support, this active crystal plane resulted in the most widely dispersed Au nanoparticles on the CeO2 support. The catalytic performance of the CeO2-supported Au catalysts for both oxidation reactions improved as the reducibility increased to generate lattice oxygen vacancies and the number of adsorbed peroxide species on the CeO2 support increased due to addition of Au. The Au catalyst on the CeO2 support prepared at 120°C was the most active in both propene/toluene/CO oxidation and independent CO oxidation.